2008
DOI: 10.1016/j.ccr.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Cancer Cells Is Maintained by EGFR Independent of Its Kinase Activity

Abstract: Expression of the epidermal growth factor receptor (EGFR), a receptor tyrosine kinase associated with cell proliferation and survival, is overactive in many tumors of epithelial origin. Blockade of the kinase activity of EGFR has been used for cancer therapy; however, by itself, it does not seem to reach maximum therapeutic efficacy. We report here that in human cancer cells, the function of kinase-independent EGFR is to prevent autophagic cell death by maintaining intracellular glucose level through interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
422
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(444 citation statements)
references
References 44 publications
(43 reference statements)
21
422
1
Order By: Relevance
“…In contrast, gefitinib-resistant cells exhibited no measurable changes in FDG uptake, either in cell culture or in vivo (Su et al, 2006). Recent findings (Weihua et al, 2008) have suggested that overexpression of EGFR is associated with tumour cell proliferation and survival, and this was attributed to maintaining the intracellular glucose level through interaction and stabilisation of the sodium/glucose cotransporter 1 (SGLT1). This suggests that inhibition of the EGFR kinase activity for cancer therapy may not provide the expected efficacy (Weihua et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gefitinib-resistant cells exhibited no measurable changes in FDG uptake, either in cell culture or in vivo (Su et al, 2006). Recent findings (Weihua et al, 2008) have suggested that overexpression of EGFR is associated with tumour cell proliferation and survival, and this was attributed to maintaining the intracellular glucose level through interaction and stabilisation of the sodium/glucose cotransporter 1 (SGLT1). This suggests that inhibition of the EGFR kinase activity for cancer therapy may not provide the expected efficacy (Weihua et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of dominant-negative mutants can only abrogate one function of survivin at one time, whereas siRNA can interrupt all the functions of survivin simultaneously and this may reinforce the inhibitory effect on the functions of survivin. 26 To date, several survivin isoforms have been reported, but the detailed biological function and mechanism are still not elucidated clearly. Given the fact that survivin is overexpressed in HCC tissue, we concluded that all survivin isoforms existing in HCC are promising targets for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 As a result, activated PanP-DM1 only showed minimal dosedependent inhibitory activity in these cell lines (Fig 3C), which is equal to that of a control ADC, anti-tumor necrosis factor (TNF) mAb-DM1. Only activated PanP-DM1 at a high concentration (1 mg/ml) inhibited the growth of BT-474 or MCF-7 cells, indicating a non-specifically inhibitory effect.…”
Section: Panp-dm1 Has Superior In Vitro Anti-tumor Activity Compared mentioning
confidence: 93%